2007
DOI: 10.1002/ijc.22922
|View full text |Cite
|
Sign up to set email alerts
|

The 8.1 ancestral MHC haplotype is strongly associated with colorectal cancer risk

Abstract: Many recent data indicate that some alleles encoded in the central major histocompatibility complex (MHC) region (Class III) of short arm of chromosome 6 may modify the risk of cancer development. Therefore we determined 4 single nucleotide polymorphisms (SNPs) of this region (TNF‐α −308 G > A, RAGE −429 T > C, HSP70‐2 −1267 A > G, LTA 252 A > G) in genomic DNA samples from 183 Hungarian patients with colorectal cancer and 141 age matched control subjects representing the Hungarian population of the same age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 39 publications
(49 reference statements)
3
21
0
Order By: Relevance
“…The fact that TNF Ϫ308A allele is a "high expressor" allele [35,52] explains the immunological basis of its association with the inflammatory stage of pathogenesis of T1D to some extent. Caucasian T1D patients exhibit a strong association of an ancestral haplotype AH8.1 that carries this high expressor allele [53,54]. It is important to note that the population frequency of TNF Ϫ308A in the Caucasian population is around 17-22% [55], higher than that observed in the Asian populations, in which it is very rare, ϳ1-3% [48,56].…”
Section: Discussionmentioning
confidence: 96%
“…The fact that TNF Ϫ308A allele is a "high expressor" allele [35,52] explains the immunological basis of its association with the inflammatory stage of pathogenesis of T1D to some extent. Caucasian T1D patients exhibit a strong association of an ancestral haplotype AH8.1 that carries this high expressor allele [53,54]. It is important to note that the population frequency of TNF Ϫ308A in the Caucasian population is around 17-22% [55], higher than that observed in the Asian populations, in which it is very rare, ϳ1-3% [48,56].…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, our data are consistent with the current understanding of the roles of 8.1AH in the inflammatory response. 8.1AH has indeed been associated with excessive and uncontrolled inflammation in various inflammatory disorders [18,19]. In CF, inflammation is believed to drive the progressive destruction of the lung and the decline in lung function which is responsible for the major morbidity and mortality [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested a positive association between the polymorphisms in cytokines and the risk of CRC. 38,39 In this metaanalysis, we analyzed the relationship between the polymorphism of TNF-a-308 G4A and the susceptibility to CRC. However, no significant association was observed.…”
Section: Main Characteristics Of Included Studiesmentioning
confidence: 99%